The covered route on rethinking Statistics classroom: a navigation through creative insubordination - Samá, Suzi; Novaes, Diva Valério (International Journal for Research in Mathematics Education, 2020)
This paper reports the route taken along the being and doing of teachers, seeking to overcome the reproductive processes of teaching statistics. It sails the waves of Creative Insubordination, towards a pedagogical practice based on the studies of Biology, Cognitive Neuroscience and Socio-Emotional Education. To this end, the text aims to present pedagogical activities committed to social justice in the Statistics classroom and designed to promote the formation of a critical, ethical, democratic and collaborative subject. This practice was built in a movement made up of reflection waves that made it possible to rethink the teaching practice in order to lead students to understand the interrelationships of statistics with the different aspects of life in society. Pedagogical activities planned through research and contextualization can provide students to understand the statistical concepts, as well as aspects of their personal formation, such as self-knowledge, social awareness, ethics and balance in relationships with themselves, with other human beings and with own life.